Theoretical and methodological substantion of the essence of corporate dispute and the peculiarities of its jurisdiction - Verbitska, Mariana; Vakiriak, Vladyslav (Actual problems of law (Aktual'ni problemi pravoznavstva), 2019)
The trend to the emergence of the significant quantity of business entities and, as a result, active development of corporate legal relationships is observed on the modern stage of the legal development of the market economy. As a result of activity, there arise different discrepancies, disputes concerning the activity of the entity between participants of the business entities. Thus, it is clear that the interests and rights of the representatives of the corporate dispute at their consideration in the economic court should be studied in the context of corporate legal relationships. Theoretic and methodological substantiation of the essence and peculiarities of the corporate dispute and criteria of jurisdiction is carried out in the article.Part 1 of Article 167 of the Commercial Code of Ukraine stipulates that corporate rights are the rights of a person whose share is determined in the statutory fund (property) of an economic organization, which includes the power to participate in the management of an economic organization, obtaining a certain share of profit (dividends) of the organization and assets in case of liquidation of the latter in accordance with the law, as well as other powers stipulated by law and statutory documents.Consequently, corporate relations are related to the implementation of corporate rights, determined by the corresponding share in the authorized fund.Corporate relations arise, change and cease on corporate rights from the moment of the state registration of a limited liability company, and in its subject composition are those that arise between an economic partnership and its participant (founder), including a participant who left, as well as between the participants (founders) of business associations, which are related to the creation, operation, management and termination of the activity of this company (except labor).It is set up that the specificity of this type of dispute is due to the fact that they require qualifications, experience and relevant knowledge in the area of corporate law, as well as in the context of other related areas of law.Corporate disputes are a separate kind of dispute, therefore it is not expedient to identify corporate disputes with other disputes of society, which, although they result from their direct activities, but are not corporate.